Two new species of the deep-sea squat lobster genus Munida Leach, 1820 (Crustacea: Decapoda: Munididae) from Taiwan: morphological and molecular evidence - Cabezas, Patricia; Lin, Chia-Wei; Chan, Tin-Yam (Zootaxa, 2011)
The genus Munida Leach, 1820 is the most diverse group within the squat lobsters, with approximately 250 described species. The extreme morphological similarity among certain species makes very difficult to identify diagnostic characters, and the real diversity of the group is probably underestimated. Here, two new species of the genus Munida from Taiwan previously identified as M. distiza Macpherson, 1994 and M. militaris Henderson, 1885, respectively, are described and illustrated. The two species are identified by subtle and constant morphological differences, which match clear molecular divergences in the 16S and COI genes. These results confirm the taxonomic value of slight morphological differences, and emphasize the need for more detailed analysis to clarify the phylogenetic relationships within the genus.